Cardiac computed tomographic angiography in patients with acute chest pain and moderately-increased troponin - Grüttner, Joachim; Haghi, Dariusch; Henzler, Thomas; Kraus, Susanne Pauline; Borggrefe, Martin; Schönberg, Stefan; Fink, Christian; Walter, Thomas (In vivo, 2012)
Aim: The aim of the study was to investigate patients with undefined chest pain and moderately increased troponin based on the results of cardiac computed tomographic (CT) angiography (CCTA). Patients and Methods: We analysed the cases of 43 patients with acute chest pain and moderately increased troponin in whom CCTA was performed. Patients with suspected stenosis on CCTA underwent percutaneous coronary angiography (PCA). Results: CCTA ruled-out significant coronary stenosis in 32 patients. Eleven patients had suspected significant coronary stenosis on CCTA. Ten patients underwent PCA, which verified significant coronary lesions in nine. Out of these, four patients were treated by percutaneous coronary intervention (PCI). One patient had to undergo coronary artery bypass grafting. A triple-rule-out CT protocol was performed in 18 patients, demonstrating pulmonary embolism in three and pericardial effusion of unknown origin in two. Conclusion: CCTA accurately identifies or rules out patients with undefined chest pain and moderately elevated troponin, which require PCA and allows detection of other significant clinical findings.
Gesehen am 28.06.2018
DOI nicht vorhanden